De la criminalisation à la légalisation des drogues : de Charybde en Scylla ? - Beauchesne, Line (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
If the drugs now considered illegal were legalized, what difficulties would have to be resolved? To answer this question, this article first points out the limitations of a policy of decriminilization in the case of soft drugs; it then shows that today, legalization and marketing of legal drugs go hand in hand and that this is a dangerous model for the legalization of drugs. Hence although the need to legalize all drugs in order to alleviate the present problems caused by their criminalization is easy enough to demonstrate, to find a model of legal distribution of drugs that avoids the negative consequences of the present policies regarding legal drugs is much more difficult. It merits some thought.